Digital Bridges: Integrating AI to Transform Healthcare Accessibility - Kavitha P. Das; Parshad Mehta (Global Journal of Medicine and Public Health, 2025)
ABSTRACT The future of healthcare is evolving rapidly, moving beyond the confines of traditional hospital walls. This paper presents a vision for care delivery through the integration of artificial intelligence, telehealth, mobile technologies, and decentralized diagnostic tools. These innovations support a shift toward proactive, preventive, and continuous care that can be delivered virtually and adapted to the needs of diverse populations. Such models hold particular promise for regions with limited access to physical healthcare infrastructure. By harnessing data-driven tools for early detection, remote monitoring, and personalized health communication, virtual ecosystems enable timely interventions and improved care coordination. This paper explores options that underpin this transformation, outlines the barriers to widespread adoption, and offers broad strategies to support the ethical and inclusive expansion of digital health ecosystems in the years ahead.